Photosensitive self-repairing microcapsule based on microfluidic technology and preparation method thereof

Through microfluidic control technology, photosensitive microcapsules with uniform size and controllable size were prepared, which solved the problem of poor controllability of emulsified droplets in the prior art, improved the repair ability of microcapsules, and achieved efficient contactless repair of epoxy resin materials.

CN119793347APending Publication Date: 2025-04-11STATE GRID JIANGSU ELECTRIC POWER CO LTD RESEARCH INSTITUTE +3
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411768272.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the preparation of existing microcapsules, the controllability of emulsified droplets is poor, which affects the size and properties of the microcapsules, and thus affects the repair effect of the material.

Method used

Microfluidic control technology is used to adjust the flow rate of the two phases to form a photosensitive microcapsule with uniform size and controllable size. The specific steps include injecting the aqueous phase and the oil phase on the PDMS-based microfluidic chip, adjusting the flow rate of the oil phase to 20-25 μL/min, and the flow rate ratio of the aqueous phase to the oil phase is 22-25:1, obtaining an O/W emulsion, and adding Fe3O4@SiO2 magnetic nanoparticles and 1,4-butanediol, and drying to obtain microcapsules.

Benefits of technology

The size uniformity and controllability of microcapsules are achieved, the repair ability of microcapsules is improved, and contactless repair can be achieved through strong light irradiation when epoxy resin material is damaged.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793347A_ABST
    Figure CN119793347A_ABST
Patent Text Reader

Abstract

The invention discloses a photosensitive self-repairing microcapsule based on a microfluidic technology and a preparation method of the photosensitive self-repairing microcapsule. The preparation method comprises the following steps: taking gum arabic (GA) and amphiphilic TiO2 as a continuous phase; the preparation method comprises the following steps: taking alicyclic photosensitive resin as a core material, and mixing the alicyclic photosensitive resin with a toluene-2, 4-diisocyanate (TDI) prepolymer to serve as a dispersion phase; oil-in-water (O / W) emulsion is collected based on a microfluidic technology, and the size of liquid drops is accurately controlled by adjusting the two-phase flow velocity; 1, 4 butanediol (BDO) is added into the emulsion to react with the TDI prepolymer to generate a polyurethane shell, meanwhile, Fe3O4 coated SiO2 nanoparticles are added, so that the microcapsule has a magnetic targeting function, agglomeration is reduced, and finally the photosensitive microcapsule which is uniform and controllable in particle size and has a self-repairing function is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microcapsule self-repairing materials, and specifically relates to a photosensitive self-repairing microcapsule based on microfluidic technology and a preparation method thereof. Background Art

[0002] Epoxy resin is an indispensable insulating material in the manufacture of high-voltage switches, transformers, motors, generators and other power equipment. However, when faced with high mechanical stress and high electric fields, tiny surface scratches or cracks, as well as internal discharge damage, may occur, which may have a significant impact on the overall performance and safety of the material.

[0003] Microcapsules are a type of smart material that contains a core of active substances and a protective shell. Due to its unique encapsulation characteristics, it is widely used in the self-repair of materials. The main principle is: before the material solidifies, the microcapsules are mixed and embedded with the material. When external stimuli appear, the shell of the microcapsule is damaged and the repair agent inside flows out to fill the cracks, a polymerization reaction occurs, and the cracks are repaired, thereby reducing economic losses and extending the service life of the material. At present, in the preparation process of microcapsules, an essential step is to form emulsified droplets. Now it is mainly formed by mechanical stirring to form a water-in-oil system. The droplets obtained in this way have poor controllability. The size of the droplets formed directly determines the size of the microcapsules, which affects the properties of the microcapsules and the subsequent material repair and polymerization reactions. Therefore, it is necessary to conduct research on the controllability of emulsified droplets, which can improve the repair ability of microcapsules and reduce economic losses, and has great engineering significance. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing photosensitive self-repairing microcapsules based on microfluidic technology.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] Deionized water, gum arabic, amphiphilic N-TiO 2 Stir evenly according to a mass ratio of 10:0.8-0.85:0.2-0.25 to obtain an aqueous phase;

[0009] Toluene-2,4-diisocyanate prepolymer, oily solvent chlorobenzene, and alicyclic photosensitive resin are uniformly stirred in a mass ratio of 0.2-0.25:0.1:1 to obtain an oil phase;

[0010] The water phase and the oil phase are introduced into the injection port of the PDMS-based microfluidic chip, the water phase is injected in equal amounts through the two continuous phase injection ports, and the oil phase is injected through the dispersed phase injection port, the flow rate of the oil phase is adjusted to 20-25 μL / min, and the flow rate ratio of the water phase to the oil phase is 22-25:1, to obtain an O / W emulsion;

[0011] Fe 3 O 4 @SiO 2 The magnetic nanoparticles are added to the O / W emulsion, 1,4-butanediol is added after dispersion treatment, heated in a water bath and stirred, and finally dried to obtain microcapsules;

[0012] Wherein, the N-TiO 2 It is nitrogen-doped titanium dioxide; the addition amount of the 1,4-butanediol is 10-12wt% of the O / W emulsion.

[0013] As a preferred solution of the method for preparing photosensitive self-repairing microcapsules based on microfluidic technology described in the present invention, the stirring speed of the aqueous phase is 500-600 r / min, and the stirring time of the aqueous phase is 2-2.5 h.

[0014] As a preferred solution of the method for preparing photosensitive self-repairing microcapsules based on microfluidic technology described in the present invention, the stirring speed of the oil phase is 400-500 r / min, and the stirring time of the oil phase is 1.5-2 h.

[0015] As a preferred embodiment of the method for preparing photosensitive self-repairing microcapsules based on microfluidic technology of the present invention, wherein: the Fe 3 O 4 @SiO 2 The method for preparing magnetic nanoparticles comprises:

[0016] Stir ferric chloride, trisodium citrate dihydrate and ethylene glycol evenly, add sodium acetate, heat, cool and collect Fe 2 O 3 Magnetic nanoparticles;

[0017] Fe 2 O 3 The magnetic nanoparticles were mixed evenly with concentrated ammonia and anhydrous ethanol, heated in an oil bath, and then tetraethyl orthosilicate was added and stirred evenly. The Fe 3 O 4 @SiO 2 Magnetic nanoparticles;

[0018] The mass ratio of ferric chloride, trisodium citrate dihydrate, ethylene glycol and sodium acetate is 1-1.5:2-2.2:10:2; the heating temperature is 100-110°C and the time is 2-3h; the Fe 2 O 3 The mass ratio of magnetic nanoparticles, concentrated ammonia water, anhydrous ethanol and tetraethyl orthosilicate is 1-1.5:2-2.5:10:1-1.5; the temperature of the oil bath heating is 90-100° C., and the heating time is 3-4 hours.

[0019] As a preferred embodiment of the method for preparing photosensitive self-repairing microcapsules based on microfluidic technology described in the present invention, the method for preparing nitrogen-doped titanium dioxide comprises:

[0020] After butyl titanate and anhydrous ethanol are stirred evenly, nitric acid is added to adjust the pH value of the solution, and then ammonia water is added to obtain a dispersion, which is dried and ground to obtain nitrogen-doped titanium dioxide powder.

[0021] Among them, the mass ratio of butyl titanate, anhydrous ethanol and ammonia water is 2:7-8:1; the stirring time is 1-1.5 hours; the pH value of the adjusted solution is 2-2.5; the drying temperature is 100-110° C.; and the drying time is 5-6 hours.

[0022] As a preferred embodiment of the method for preparing photosensitive self-repairing microcapsules based on microfluidic technology of the present invention, wherein: the Fe 3 O 4 @SiO 2 The added amount of magnetic nanoparticles is 0.2 to 0.5 g.

[0023] As a preferred solution of the method for preparing photosensitive self-repairing microcapsules based on microfluidic technology described in the present invention, the temperature of the water bath heating is 55-60°C.

[0024] As a preferred solution of the method for preparing photosensitive self-repairing microcapsules based on microfluidic technology described in the present invention, the water bath heating time is 1 to 1.5 hours.

[0025] Another object of the present invention is to overcome the deficiencies in the prior art and provide a photosensitive self-repairing microcapsule prepared by a photosensitive self-repairing microcapsule preparation method based on microfluidic technology.

[0026] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for using a photosensitive self-repairing microcapsule based on microfluidic technology in repairing epoxy resin materials.

[0027] Beneficial effects of the present invention:

[0028] Based on the microfluidic experimental platform built on micro-controlled flow technology, by adjusting the two-phase flow rate, the optimal droplet particle size is found, and a photosensitive microcapsule with uniform and controllable size is developed. The photosensitive microcapsule is compounded with epoxy resin. When the epoxy resin is damaged, strong light can be used to repair the damage without contact. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0030] Figure 1 This is a diagram of the microfluidic experimental platform in Example 1 of the present invention;

[0031] Figure 2 This is a schematic diagram of the preparation principle of microcapsules in Example 1 of the present invention;

[0032] Figure 3 This is a scanning electron microscope (SEM) image of the microcapsules prepared in Example 1 of the present invention;

[0033] Figure 4 Fe prepared in Example 1 of the present invention 2 O 3 Magnetic nanoparticles and Fe 3 O 4 @SiO 2 Magnetic induction intensity curve of magnetic nanoparticles;

[0034] Figure 5 The particle size diagram of the O / W droplets prepared in Example 1 of the present invention and Comparative Example 1;

[0035] Figure 6 The morphology of the microcapsules prepared in Example 1 and Comparative Example 2 of the present invention after illumination;

[0036] Figure 7 The morphology of the microcapsules prepared in Comparative Examples 2 and 3 of the present invention after illumination;

[0037] Figure 8 This is a scanning electron microscope (SEM) image of the microcapsules prepared in Comparative Example 4 of the present invention;

[0038] Fig. 9 This is a diagram of the electrical tree initiation probability of the epoxy resin used in Test Example 1 of the present invention and the prepared composite epoxy resin. DETAILED DESCRIPTION

[0039] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0040] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0041] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0042] The alicyclic photosensitive resin used in the present invention is analytically pure, Sigma Aldrich brand, model ERL-4221 / PI6992, epoxy equivalent of 129.0-138.0 g / Eq, chromaticity (Pt-Co) 100max, specific gravity @25C1.159-1.174 g / cm 3 .

[0043] The nano-TiO used in the present invention 2 The purity of the particles is 99%; the density of gum arabic is 1.35 g / mL; the solid content of the prepolymer (TDI) is 75% and the viscosity is 1600.

[0044] The model of the diluent benzyl glycidyl ether used in the present invention is 692AGE.

[0045] The model of the bisphenol A epoxy resin (DGEBA) used in the present invention is WSR618 (E-51).

[0046] The model of the methyltetrahydrophthalic anhydride curing agent (MTHPA) used in the present invention is DMP-30.

[0047] The method for testing the probability of electrical tree initiation of the present invention is as follows: 30 groups of pure epoxy resin materials and composite epoxy resin materials are prepared respectively, a partial discharge test platform is built to apply voltage to the materials, and the voltage is gradually increased by 0.6 kV each time until electrical tree appears in the materials, the switch is opened, and the number of voltages is recorded to obtain statistical rules.

[0048] The testing method of the magnetic induction intensity of the present invention is: using a vibrating sample magnetometer (model 7407) to measure the magnetic induction intensity of the sample based on the electromagnetic induction principle.

[0049] Preparation method of microfluidic chip: attach silicon wafer to the turntable of glue machine, rotate the turntable of glue machine after vacuuming, then heat the silicon wafer with photoresist, then irradiate with ultraviolet light and heat again, clean the fluorinated silicon wafer, and form a cross channel protrusion chip model; mix polydimethylsiloxane and platinum catalyst evenly, perform vacuum degassing treatment, pour into the chip model, then heat and cure, punch and cut to obtain polydimethylsiloxane block, and plasma treat the block and quartz sheet together to finally obtain microfluidic chip. Among them, the vacuuming time is 15min, the rotation time of the glue machine turntable is 10min; the heating temperature is 100℃, the heating time is 35min; the heating curing temperature is 55℃, the heating curing time is 5h; the plasma treatment is 50s; the mass ratio of polydimethylsiloxane to platinum catalyst is 10:1.

[0050] Reference Figure 1 , build the platform: connect the three injection ports of the microfluidic chip to the injection pumps of two continuous phases and one dispersed phase respectively, place a camera above the chip to take pictures of the process of water phase cutting oil phase, and guide the cut droplets to the droplet collection container through the PTFE catheter.

[0051] Example 1

[0052] This embodiment provides a method for preparing photosensitive self-repairing microcapsules based on microfluidic technology, specifically:

[0053] (1) Preparation of Fe 3 O 4 @SiO 2 Magnetic nanoparticles: Mix ferric chloride, trisodium citrate dihydrate, and ethylene glycol, add sodium acetate, and heat at 100°C for 2h. After cooling, collect Fe 2 O 3 Magnetic nanoparticles. The mass ratio of ferric chloride, trisodium citrate dihydrate, ethylene glycol and sodium acetate is 1:2:10:2.

[0054] Fe 2 O 3 The magnetic nanoparticles were mixed with concentrated ammonia and anhydrous ethanol and heated in an oil bath at 90°C for 3 h. Then tetraethyl orthosilicate was added and stirred evenly. The Fe 3 O 4 @SiO 2 Magnetic nanoparticles.

[0055] Among them, Fe 2 O 3 The mass ratio of magnetic nanoparticles, concentrated ammonia water, anhydrous ethanol and tetraethyl orthosilicate is 1:2:10:1.

[0056] (2) Preparation of N-TiO 2 : After stirring butyl titanate and anhydrous ethanol for 1 hour, nitric acid was added and the pH value of the solution was adjusted to 2, and then ammonia water was added to obtain a dispersion, which was dried at 100°C for 5 hours and ground to obtain nitrogen-doped titanium dioxide powder. The mass ratio of butyl titanate, anhydrous ethanol and ammonia water was 2:7:1.

[0057] (3) Preparation of microcapsules: Deionized water, gum arabic, amphiphilic N-TiO 2 The mixture was stirred for 2 h in a ratio of 10:0.8:0.2 to obtain an aqueous phase.

[0058] Toluene-2,4-diisocyanate (TDI) prepolymer, oily solvent chlorobenzene, and alicyclic photosensitive resin were stirred at a ratio of 0.2:0.1:1 at a rotation speed of 400 r / min for 1.5 hours to obtain an oil phase.

[0059] The water phase and the oil phase were introduced into the injection port of the microfluidic chip at a volume ratio of 300:1, wherein the water phase was injected in equal amounts through the two continuous phase injection ports, and the oil phase was injected through the dispersed phase injection port, and the flow rates of the two phases were adjusted to obtain an O / W emulsion. Among them, the oil phase flow rate Q d =25μL / min, the flow rate ratio of water phase to oil phase is Q c / Q d =25:1.

[0060] Next, 0.2 g of Fe 3 O 4 @SiO 2 The magnetic nanoparticles were added to the O / W emulsion, and after dispersion treatment, 15 mL of 1,4-butanediol (BDO) was added, and the mixture was heated and stirred in a water bath at 55° C. for 1 h, and finally dried to obtain microcapsules.

[0061] The microcapsules prepared in Example 1 were tested by scanning electron microscopy (SEM). Figure 3 As shown in the figure, it can be seen that the method successfully prepared microcapsules with uniform particle size, and the size of the microcapsules was 145-155 μm.

[0062] The Fe prepared in Example 1 2 O 3 Magnetic nanoparticles and Fe 3 O 4 @SiO 2 The magnetic properties of magnetic nanoparticles were measured. Figure 4 shown.

[0063] from Figure 4 It can be seen that Fe 3 O 4 @SiO2 The saturation magnetization is 33.54emu / g, Fe 3 O 4 The saturation magnetization of SiO is 59.24emu / g, indicating that 2 With reduced Fe 3 O 4 The function of affecting the insulation and stability of the matrix material is indispensable in the production of microcapsules.

[0064] Example 2

[0065] This embodiment provides a method for preparing photosensitive self-repairing microcapsules based on microfluidic technology, specifically:

[0066] (1) Preparation of Fe 3 O 4 @SiO 2 Magnetic nanoparticles: Stir ferric chloride, trisodium citrate dihydrate and ethylene glycol evenly, add sodium acetate, and heat at 110 ° C for 2 h. After cooling, collect Fe 2 O 3 Magnetic nanoparticles. The mass ratio of ferric chloride, trisodium citrate dihydrate, ethylene glycol and sodium acetate is 1.5:2.2:10:2.

[0067] Fe 2 O 3 The magnetic nanoparticles were mixed with concentrated ammonia and anhydrous ethanol and heated in an oil bath at 90°C for 3 h. Then tetraethyl orthosilicate was added and stirred evenly. The Fe 3 O 4 @SiO 2 Magnetic nanoparticles.

[0068] Among them, Fe 2 O 3 The mass ratio of magnetic nanoparticles, concentrated ammonia water, anhydrous ethanol and tetraethyl orthosilicate is 1.5:2:10:1.

[0069] (2) Preparation of N-TiO 2 : After stirring butyl titanate and anhydrous ethanol for 1.5 hours, nitric acid was added and the pH value of the solution was adjusted to 2, and then ammonia water was added to obtain a dispersion, which was dried at 110°C for 5 hours and ground to obtain nitrogen-doped titanium dioxide powder. The mass ratio of butyl titanate, anhydrous ethanol and ammonia water was 2:8:1.

[0070] (3) Preparation of microcapsules: Deionized water, gum arabic, amphiphilic N-TiO 2 The mixture was stirred for 2 h in a ratio of 10:0.85:0.25 to obtain an aqueous phase.

[0071] Toluene-2,4-diisocyanate (TDI) prepolymer, oily solvent chlorobenzene, and alicyclic photosensitive resin were stirred at a ratio of 0.25:0.1:1 at a rotation speed of 400 r / min for 1.5 hours to obtain an oil phase.

[0072] The water phase and the oil phase were introduced into the injection port of the microfluidic chip at a volume ratio of 300:1, wherein the water phase was injected in equal amounts through the two continuous phase injection ports, and the oil phase was injected through the dispersed phase injection port, and the flow rates of the two phases were adjusted to obtain an O / W emulsion. d =23μL / min, the flow rate ratio of water phase to oil phase is Q c / Q d =22:1.

[0073] Next, 0.3 g of Fe 3 O 4 @SiO 2 The magnetic nanoparticles were added to the O / W emulsion, and after dispersion treatment, 20 mL of 1,4-butanediol (BDO) was added, and the mixture was heated and stirred in a water bath at 55° C. for 1 h, and finally dried to obtain microcapsules.

[0074] The microcapsules prepared in this example have similar effects to those prepared in Example 1. After damage occurs, the damage causes the microcapsules to rupture, which are then cured and repaired under light.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 1 is that the flow rate ratio Q of the water phase to the oil phase in step (3) is adjusted to c / Q d The ratio of the molar ...

[0077] The particle sizes of the O / W droplets prepared in Example 1 and Comparative Example 1 were measured. The results are as follows: Figure 5 shown.

[0078] from Figure 5 It can be seen that as the proportion of the continuous phase increases, the frequency of the water phase cutting the oil phase increases, and the droplet size gradually decreases. However, when the proportion of the continuous phase is too large, its utilization rate decreases, and the droplet size will not decrease indefinitely, and the falling speed tends to saturation. It can be seen that the preparation method of the present invention can select a suitable particle size by regulating the flow rate ratio of the two phases, so as to achieve the effect of repairing the material after the microcapsule is illuminated.

[0079] Comparative Example 2

[0080] The difference between this comparative example and Example 1 is that the N-TiO 2 TiO 2The rest of the preparation process is the same as that in Example 1 to prepare microcapsules.

[0081] Comparative Example 3

[0082] The difference between this comparative example and Example 1 is that TiO 2 The rest of the preparation process is the same as that in Example 1 to prepare microcapsules.

[0083] The microcapsules prepared in Example 1 and Comparative Examples 2-3 were irradiated with light for the same time, and the morphology of the microcapsules after irradiation was observed. The results are as follows: Figures 6-7 shown.

[0084] Depend on Figure 6 It can be seen that when damage occurs, the use of N-TiO 2 After the microcapsules are exposed to light, the repair agent flows out more quickly and more. 2 After exposure to light, the repair agent outflow rate of the microcapsules is faster than that of N-TiO 2 This indicates that TiO 2 Nitrogen doping can enhance the photocatalytic performance and make the microcapsules repair faster.

[0085] Depend on Figure 7 It can be seen that when damage occurs, the addition of TiO 2 After exposure to light, the microcapsules have a repair agent flowing out and can be repaired. 2 After the microcapsules were exposed to light, the repair agent had solidified inside the capsules, and the damage could not be repaired without the repair agent flowing out. This shows that the TiO 2 It is extremely important for the construction of microcapsules. 2 The microcapsules can be shielded from light, the stability of the core material can be maintained, and the phenomenon of the microcapsules being cured due to ultraviolet rays causing the photosensitive core material to be prevented from being cured.

[0086] Comparative Example 4

[0087] The difference between this comparative example and Example 1 is that the microcapsules are not prepared based on microfluidic technology, but the water phase and the oil phase are mixed by mechanical stirring to prepare the microcapsules.

[0088] The microcapsules prepared in Comparative Example 4 were tested by scanning electron microscopy (SEM). Figure 8 shown.

[0089] Depend on Figure 8 It can be seen that when microfluidic technology is not used to prepare microcapsules, the obtained microcapsules have serious agglomeration phenomenon and the particle sizes of microcapsules are different, which is likely to affect the subsequent repair effect, verifying the superiority of microfluidic technology in the microcapsule production process.

[0090] Test Example 1

[0091] The microcapsules prepared in Implementation 1 were subjected to a repair test.

[0092] Test method: bisphenol A epoxy resin (DGEBA), diluent benzyl glycidyl ether, and methyltetrahydrophthalic anhydride curing agent (MTHPA) were mixed at a mass ratio of 1:0.2 to 0.25:0.25 at a speed of 900 r / min, and then poured into a metal mold after vacuuming for 10 minutes, and the microcapsules prepared in Example 1 were added, and heated at 110°C for 3 hours to obtain a composite epoxy resin. A 20kV industrial frequency power was applied to the composite epoxy resin and the epoxy resin without the microcapsules in Example 1, and the initiation probability of electrical treeing of the two epoxy resins was observed. The results are as follows: Fig. 9 shown.

[0093] contrast Fig. 9 The initiation probability of electric treeing of the two epoxy resins can be seen, and it is found that the initiation voltage of the two is basically the same, indicating that the addition of microcapsules will not increase the "impurities" in the material and affect the insulation properties of the insulating material itself.

[0094] In summary, the present invention uses a microfluidic experimental platform built based on micro-control flow technology to adjust the two-phase flow rate to find the optimal droplet size and develop a photosensitive microcapsule with uniform size and controllable size. In the preparation process, toluene-2,4-diisocyanate (TDI) prepolymer is dissolved in the oil phase, and gum arabic (GA) and amphiphilic N-TiO 2 As an emulsifier, TDI's highly reactive -NCO groups and amphiphilic N-TiO 2 Distributed at the water-oil interface, after emulsification, small oil-in-water (O / W) droplets are formed. 1,4-Butanediol (BDO) is added to it, and reacts with TDI at the interface to form a polyurethane (PU) shell, and finally photosensitive microcapsules with uniform particle size and appropriate size are obtained.

[0095] Fe was added during the preparation of microcapsules. 3 O 4 @SiO 2 Magnetic nanoparticles can give microcapsules magnetic targeting functions, reduce agglomeration, and maintain dispersion.

[0096] The photosensitive microcapsules prepared by the present invention are compounded with epoxy resin, and when the epoxy resin is damaged, the damage can be repaired contactlessly by irradiating it with strong light.

[0097] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing photosensitive self-repairing microcapsules based on microfluidic technology, characterized in that: include, Deionized water, gum arabic, and amphiphilic N-TiO2 are uniformly stirred in a mass ratio of 10:0.8-0.85:0.2-0.25 to obtain a water phase; Toluene-2,4-diisocyanate prepolymer, oily solvent chlorobenzene, and alicyclic photosensitive resin are uniformly stirred in a mass ratio of 0.2-0.25:0.1:1 to obtain an oil phase; The water phase and the oil phase are introduced into the injection port of the PDMS-based microfluidic chip, the water phase is injected in equal amounts through the two continuous phase injection ports, and the oil phase is injected through the dispersed phase injection port, the flow rate of the oil phase is adjusted to 20-25 μL / min, and the flow rate ratio of the water phase to the oil phase is 22-25:1, to obtain an O / W emulsion; Fe3O4@SiO2 magnetic nanoparticles were added to the O / W emulsion, and 1,4-butanediol was added after dispersion treatment. The mixture was heated and stirred in a water bath, and finally dried to obtain microcapsules. Wherein, the N-TiO2 is nitrogen-doped titanium dioxide; the addition amount of the 1,4-butanediol is 10 to 12 wt % of the O / W emulsion.

2. The method for preparing photosensitive self-repairing microcapsules based on microfluidic technology according to claim 1, characterized in that: The stirring speed of the water phase is 500-600 r / min, and the stirring time of the water phase is 2-2.5 h.

3. The method for preparing photosensitive self-repairing microcapsules based on microfluidic technology according to claim 1, characterized in that: The stirring speed of the oil phase is 400-500 r / min, and the stirring time of the oil phase is 1.5-2 h.

4. The method for preparing photosensitive self-repairing microcapsules based on microfluidic technology according to claim 1, characterized in that: The preparation method of the Fe3O4@SiO2 magnetic nanoparticles comprises: Ferric chloride, trisodium citrate dihydrate and ethylene glycol were stirred evenly, sodium acetate was added, and the mixture was heated, and Fe2O3 magnetic nanoparticles were collected after cooling; The Fe2O3 magnetic nanoparticles were mixed with concentrated ammonia and anhydrous ethanol and then heated in an oil bath, and then tetraethyl orthosilicate was added and stirred evenly to finally prepare Fe3O4@SiO2 magnetic nanoparticles. Among them, the mass ratio of ferric chloride, trisodium citrate dihydrate, ethylene glycol and sodium acetate is 1-1.5:2-2.2:10:2; the heating temperature is 100-110°C, and the time is 2-3h; the mass ratio of Fe2O3 magnetic nanoparticles, concentrated ammonia water, anhydrous ethanol and tetraethyl orthosilicate is 1-1.5:2-2.5:10:1-1.5; the oil bath heating temperature is 90-100°C, and the time is 3-4h.

5. The method for preparing photosensitive self-repairing microcapsules based on microfluidic technology according to claim 1, characterized in that: The preparation method of the nitrogen-doped titanium dioxide comprises: After butyl titanate and anhydrous ethanol are stirred evenly, nitric acid is added to adjust the pH value of the solution, and then ammonia water is added to obtain a dispersion, which is dried and ground to obtain nitrogen-doped titanium dioxide powder. Among them, the mass ratio of butyl titanate, anhydrous ethanol and ammonia water is 2:7-8:1; the stirring time is 1-1.5 hours; the pH value of the adjusted solution is 2-2.5; the drying temperature is 100-110° C.; and the drying time is 5-6 hours.

6. The method for preparing photosensitive self-repairing microcapsules based on microfluidic technology according to claim 1, characterized in that: The added amount of the Fe3O4@SiO2 magnetic nanoparticles is 0.2-0.5g.

7. The method for preparing photosensitive self-repairing microcapsules based on microfluidic technology according to claim 1, characterized in that: The water bath heating temperature is 55-60°C.

8. The method for preparing photosensitive self-repairing microcapsules based on microfluidic technology according to claim 1, characterized in that: The water bath heating time is 1 to 1.5 hours.

9. A photosensitive self-repairing microcapsule based on microfluidic technology prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the photosensitive self-repairing microcapsules based on microfluidic technology as claimed in claim 9 in repairing epoxy resin materials.

Citation Information

Cited By

  • Biomass-based humidity-sensitive repair recoverable fluorescent adjustable microcapsule and preparation method thereof

    CN121271532A